Концепции медиареальности как теоретико-методологическая основа библиотековедческой реальности (Библиосфера, 2010)
Problems of mediareality in the field of library science are considered. The notion «reality» as a general theoretical basis for the study of library activity is analyzed. The notion of «library science reality» is revealed.